The Countercultural Victory of 1 John in Greco-Roman Context: Conquering the World - Kim, Ahreum (The Library of New Testament Studies, 2023)
Cover -- Series -- Title -- Copyright -- Contents -- Figures -- Tables -- Acknowledgments -- Abbreviations -- 1 Introduction -- 2 Victory in the Greco-Roman World -- 3 The Conquered -- 4 A Countercultural Letter -- 5 Conquering the World with Pistis -- 6 Conclusion and Final Reflections -- Bibliography -- Index of References.